Germination in vitro, genetic diversity and mating system of Cedrela fissilis Vell, in central Brazil - Diaz-Soto, Juan Manuel (2018)
In northern Minas Gerais state, there is an ecotone formed by the junction of three vegetation formations, Atlantic dry forest, Cerrado, and Caatinga. This region is threatened by over-logging and habitat destruction. Several tropical tree species native to this ecotone are endangered by extinction, subject to overexploitation and habitat loss. Cedrela fissilis is a tropical tree species native to Brazil and distributed in seasonal forests and gallery forests of northern Minas Gerais. In this study, we analyzed the genealogical placement of a population from northern Minas Gerais (PAN) related to the two known lineages (East and West) of C. fissilis and carry out genetic structure and mating system analyses of its offspring. To obtain tissue from seedling suitable for DNA extraction we tested three disinfection methods, four culture media and a commercial substrate for plants. The results showed that the application of in- vitro techniques jointly with disinfection increased the germination by a factor from 3 to 5 with respect to the non-use of in-vitro techniques, and the double disinfection increased the germination by a factor of 1.7 respect of the simple disinfection. We found high values of genetic diversity that differentiate from both the East and West lineages; thus, PAN can be considered as a new source of variability within C. fissilis. The results confirmed that C. fissilis is as an outcrossed species with some proportion of selfing. PAN presented mating among relatives, and population structure among offspring as a consequence of deviations from random mating. We concluded that restrictions to gene-flow among reproductive trees lead to the high levels of genetic differentiation observed in PAN.